Pengembangan Asesmen Pembelajaran PAI Pada Lembaga Pendidikan Tinggi Islam dalam Era Digital - Desi Rianasari; Helmi Rizal Taupik; Ratu Asma; Umar Mone; Arman Paramansyah (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
The development of science and technology is a challenge for islamic education, especially in facing the era of globalization which has been able to systematize distance and time between various countries in exchanging information and knowledge. The rapid development of Islamic Religious Education, both in curriculum and in learning, encourages educational institutions, educators, (teachers or lecturers) to be able to improve their learning in Islamic Religious Education. This research is a literature study using qualitative methods whose research results in the Digital Era facilitate and foster learning interest and creativity of students (students and students) in developing learning materials for Islamic Religious Education. Keywords:Science and Technology, globalization, Islamic Religious Education,Curruculum, Qualitative , Digital Era.